1996
DOI: 10.1142/s0218625x96001959
|View full text |Cite
|
Sign up to set email alerts
|

OPTICAL PROPERTIES OF CARBON CLUSTERS EMBEDDED IN SiO2 FILMS

Abstract: Raman spectra were measured for carbon-doped SiO 2 thin films prepared by an rf cosputtering method. The changes in the spectra were systematically studied as a function of the annealing temperature. From a detailed analysis of the spectra, the following conclusions were drawn. In the as-deposited films, very small carbon clusters are embedded in the SiO 2 matrices. When the films are annealed at 600°C, graphite-like sp 2 bonds begin to develop in the clusters. Upon annealing with higher temperatures, the size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The role of NPs size in describing the PL mechanisms of the SiO x C y matrix was first explained by Hayashi et al, where the role of carbon clusters in the SiO x C y matrix was discussed, concluding that carbon clusters (≈2 nm), equal to or smaller than C60, could influence PL in the 2.2 eV band. [ 147,148 ] B. Garrido et al also described the role of QDs in SiO 2 implanted with carbon and Si and explained the reason for PL at different bands such as 1.4–1.6, 2–2.2, and 2.7 eV, due to the formation of QDs (1.4–1.6 eV), amorphous carbon clusters (2‐2.2 eV), and SiC clustering (2.7 eV), respectively. [ 149–151 ] Moreover, other authors suggested as well that the formation of NCs, amorphous carbon clusters, SiC, and/or a complex of Si, O, and C such as Si y C 1− y O x complexes ( x < 2) could exert influence for PL at 1.9, 2.1, and 2.7 eV bands, respectively.…”
Section: Emission Mechanisms Of Si Nanostructures In the Carbide‐rela...mentioning
confidence: 99%
See 1 more Smart Citation
“…The role of NPs size in describing the PL mechanisms of the SiO x C y matrix was first explained by Hayashi et al, where the role of carbon clusters in the SiO x C y matrix was discussed, concluding that carbon clusters (≈2 nm), equal to or smaller than C60, could influence PL in the 2.2 eV band. [ 147,148 ] B. Garrido et al also described the role of QDs in SiO 2 implanted with carbon and Si and explained the reason for PL at different bands such as 1.4–1.6, 2–2.2, and 2.7 eV, due to the formation of QDs (1.4–1.6 eV), amorphous carbon clusters (2‐2.2 eV), and SiC clustering (2.7 eV), respectively. [ 149–151 ] Moreover, other authors suggested as well that the formation of NCs, amorphous carbon clusters, SiC, and/or a complex of Si, O, and C such as Si y C 1− y O x complexes ( x < 2) could exert influence for PL at 1.9, 2.1, and 2.7 eV bands, respectively.…”
Section: Emission Mechanisms Of Si Nanostructures In the Carbide‐rela...mentioning
confidence: 99%
“…The role of NPs size in describing the PL mechanisms of the SiO x C y matrix was first explained by Hayashi et al, where the role of carbon clusters in the SiO x C y matrix was discussed, concluding that carbon clusters (%2 nm), equal to or smaller than C60, could influence PL in the 2.2 eV band. [147,148] B. Garrido et al also described the role of QDs in SiO 2 implanted with…”
Section: Pl Mechanismsmentioning
confidence: 99%